2020
DOI: 10.1515/pac-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Excess spectroscopy and its applications in the study of solution chemistry

Abstract: AbstractCharacterization of structural heterogeneity of liquid solutions and the pursuit of its nature have been challenging tasks to solution chemists. In the last decade, an emerging method called excess spectroscopy has found applications in this area. The method, combining the merits of molecular spectroscopy and excess thermodynamic functions, shows the ability to enhance the apparent resolution of spectra, provides abundant information concerning solution structures and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…For each IR spectrum, excess spectroscopy analysis was performed using the method as described elsewhere [ 10 , 82 , 83 ]. Briefly, excess absorption is defined as the residual between the absorption of a mixture and that of an ideal mixture: where and are the absorption coefficients of the real mixture and ideal mixture, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For each IR spectrum, excess spectroscopy analysis was performed using the method as described elsewhere [ 10 , 82 , 83 ]. Briefly, excess absorption is defined as the residual between the absorption of a mixture and that of an ideal mixture: where and are the absorption coefficients of the real mixture and ideal mixture, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, researchers mainly study the kinetic processes of forming and breaking HBs by spectroscopic methods (including IR and NMR). Examples include the following: nonideality and ionic clusters in ILs have been thoroughly studied by IR spectroscopy, 184 Tokmakoff et al revealed the unique vibration potential of the HF system in water and differentiated hydrogen bonding from chemical bonding via femtosecond IR technology, 64 and Hunger et al reported that the time scale of the vibrational spectrum of the N–H bond in [C 2 H 5 NH 3 ][NO 3 ] ranges from femtoseconds to picoseconds, indicating the Z-bond-induced complex movement of ions. 186 How to quickly detect the disruption of the Z-bond or the separation of cation–anion pairs remains a major challenge.…”
Section: Opportunities and Future Challenges Of Z-bonds And Quasi-liq...mentioning
confidence: 99%
“…The theory of excess absorption spectroscopy can be found in detail in the previous studies, ,, and a summary of the theory is provided in the Supporting Information.…”
Section: Experimental Methodsmentioning
confidence: 99%